2007
DOI: 10.1088/1478-3975/4/2/004
|View full text |Cite
|
Sign up to set email alerts
|

3D finite element analysis of uniaxial cell stretching: from image to insight

Abstract: Mechanical forces play an important role in many microbiological phenomena such as embryogenesis, regeneration, cell proliferation and differentiation. Micromanipulation of cells in a controlled environment is a widely used approach for understanding cellular responses with respect to external mechanical forces. While modern micromanipulation and imaging techniques provide useful optical information about the change of overall cell contours under the impact of external loads, the intrinsic mechanisms of energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…Matrix strain has been measured directly, or determined by using microscopy and finite element (FE) techniques. [38][39][40][41] Cells receive varying degrees of compressive strain in a direction perpendicular to the stretch axis dependent on the Poisson ratio of the membrane or scaffold. 42,43 Work in 3D FE has shown that the strain that cells actually receive can be much larger than that applied to the matrix due to variations in matrix microarchitecture.…”
Section: Cell-and Tissue-stretching Devicesmentioning
confidence: 99%
“…Matrix strain has been measured directly, or determined by using microscopy and finite element (FE) techniques. [38][39][40][41] Cells receive varying degrees of compressive strain in a direction perpendicular to the stretch axis dependent on the Poisson ratio of the membrane or scaffold. 42,43 Work in 3D FE has shown that the strain that cells actually receive can be much larger than that applied to the matrix due to variations in matrix microarchitecture.…”
Section: Cell-and Tissue-stretching Devicesmentioning
confidence: 99%
“…However, they are one of the most widespread option for ensuring the actuation of passive MEMS dedicated to the stimulation of cells. Thereby, positioning stages are conventionally used to actuate passive microstructures such as microplates (e.g., Thoumine et al, 1999;Desprat et al, 2006;Ferná ndez et al, 2006;Gladilin et al, 2007;Chan et al, 2008) or microindenters (e.g., Koay et al, 2003;Peeters et al, 2005;Sato et al, 2007).…”
Section: Micro-nanopositioning Stagesmentioning
confidence: 99%
“…Of course, this analysis requires that the cell is still connected to the cantilever after detachment from the surface. Another solution would be to covalently couple cells to the cantilever, e.g., using glutaraldehyde (35).…”
Section: Experimental Prerequisites Of Single-cell Force Spectroscopymentioning
confidence: 99%